A Direct Arylation Approach for the Preparation of Benzothiadiazole-Based Fluorophores for Application in Luminescent Solar Concentrators - Papucci, Costanza; Ventura, Francesco; Franchi, Daniele; Dessi, Alessio; Pucci, Andrea; Reginato, Gianna; Mordini, Alessandro; Calamante, Massimo; Zani, Lorenzo (Synlett, 2023)
A straightforward synthetic protocol featuring direct C–H arylations as key steps has been optimized to prepare two benzo-2,1,3-thiadiazole (BTD)-based organic fluorophores. Their light absorption and emission properties, as well as their affinity with poly(methyl methacrylate) as the chosen polymer matrix, were found to be suitable for application in luminescent solar concentrators. Solar-concentration devices were fabricated with both emitters, and their relevant optical and photovoltaic properties are presented.
Keywords: direct arylation; fluorophores; benzothiadiazoles; luminescent solar concentrator; photovoltaics